ENHANCEMENT RESULTS STUDENT LEARNING IN COMPLETION QUESTIONS SPLDV MATERIAL THROUGH IMPLEMENTATION LEARNING COOPERATIVE TUTORS PEERS - Haryanto, Edy (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research aims to determine the improvement in class student learning outcomes VII MTs. Darul Ulum Bantaran academic year 2022/2023 in completion questions on material principal SPLDV through implementation learning cooperative with tutors peer. Subject study is student class VII MTs. Darul Ulum Bantaran number 40 child ,a Teacher Mathematics And a observer. Data Which collected covers results Study student, results observation Teacher, results observation student. Study This is Classroom Action Research (PTK) which is carried out in two cycles.Each cycle includes 4 (four) stages namely planning, implementation action, observation (observation) and reflection. In this research it is said to be successful if at least 85% student obtain mark ≥ 65. The research results show: (1) Student learning completeness in cycle I was 62.50% with mark average 67.13 And on cycle II as big as 87.50% with markaverage 77.88 (2) Score activity student on cycle I as big as 70% And on cycle IIamounting to 82.50%. From the data above it clearly shows that in cycle I results Study Not yet according to expectations, which means the indicator success yet achieved while in cycle II the learning outcomes were in line with meaningful expectations indicator success already achieved.